Plasma MicroRNA Expression Profiles in Psoriasis - Shiju Xiao; Xin Liu; Xiaoxu Wang; Hongpeng Lv; Junbo Zhao; Xinwei Guo; Fuyang Xian; Yunrun Ji; Guangzhong Zhang (Journal of Immunology Research)
Background. Psoriasis is an immune-mediated inflammatory chronic skin disease characterized by chronic inflammation in the dermis, parakeratosis, and excessive epidermal growth. MicroRNAs (miRNAs) are key regulators of immune responses. Although differential expression of miRNAs has been reported in certain inflammatory autoimmune diseases, their role in psoriasis has not been fully illuminated. Our aims were to confirm plasma miRNA expression signatures in psoriasis and to examine their potential influence on psoriasis pathogenesis. Methods. A miRNome PCR array was used to analyse the plasma of psoriasis patients and healthy donors. We performed miRNA pathway enrichment and target gene network analyses on psoriasis plasma samples. Results. We found several specific plasma miRNA signatures relevant to psoriasis. The miRNAs targeted pathways associated with psoriasis, such as the VEGF, MAPK, and WNT signaling pathways. Network analysis revealed pivotal deregulated plasma miRNAs and their relevant target genes and pathways regulating psoriasis pathogenesis. Conclusions. This study analysed the expression of plasma miRNAs and their target pathways, elucidating the pathogenesis of psoriasis; these results may be used to design novel therapeutic strategies and to identify diagnostic biomarkers for psoriasis.